2012
DOI: 10.1139/g2012-066
|View full text |Cite
|
Sign up to set email alerts
|

Construction of genetic linkage map and mapping of QTL for seed color inBrassica rapa

Abstract: A genetic linkage map of Brassica rapa L. was constructed using recombinant inbred lines (RILs) derived from a cross between yellow-seeded cultivar Sampad and a yellowish brown seeded inbred line 3-0026.027. The RILs were evaluated for seed color under three conditions: field plot, greenhouse, and controlled growth chambers. Variation for seed color in the RILs ranged from yellow, like yellow sarson, to dark brown/black even though neither parent had shown brown/black colored seeds. One major QTL (SCA9-2) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 41 publications
3
35
1
Order By: Relevance
“…Heritability and the cross-environment correlation for this trait were both over 0.8, and we detected one large-effect QTL affecting only this trait on A9 in both environments. This supports previous studies mapping seed color to one or a few genes on A9 in B. rapa [23,49]. The candidate gene BrTT8 has been identified in this region and shown to control the accumulation of proanthocyanidins in the seed coat [71,72].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Heritability and the cross-environment correlation for this trait were both over 0.8, and we detected one large-effect QTL affecting only this trait on A9 in both environments. This supports previous studies mapping seed color to one or a few genes on A9 in B. rapa [23,49]. The candidate gene BrTT8 has been identified in this region and shown to control the accumulation of proanthocyanidins in the seed coat [71,72].…”
Section: Discussionsupporting
confidence: 88%
“…Brassica rapa is an internationally cultivated seed oil and vegetable crop and a parent of the hybrid-origin mustard crops, B. napus (canola) and B. juncea (Indian mustard) [47]. Numerous genetic resources have been developed for this species [22,23,48,49], and the first reference sequence for B. rapa was released in 2011 [50]. Naturalized populations of B. rapa are distributed throughout the United States and often occur in disturbed habitats or the margins of agricultural fields [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study the SNP marker SNP21195A09 was identified to the other side of the QTL peak, enabling the QTL to be clearly located on the B. rapa genome sequence. Xiao et al [39] mapped a recessive gene for seed colour on chromosome A09 in B. rapa , however the physical region containing this gene (between 19.3 and 22.1 Mbp) does not correspond to the locus identified in our study. Furthermore, Kebede et al [40] mapped a major seed colour QTL in B. rapa on the middle of A09.…”
Section: Discussioncontrasting
confidence: 86%
“…A genetic linkage map constructed based on 96 RILs of the Sampad × 3-0026.027 cross of B. rapa and by the use of simple sequence repeat (SSR) and amplified fragment length polymorphism (AFLP) markers (Kebede et al, 2012) was used to map the QTL for total seed GSL content. Composite interval mapping (CIM) using QTL Cartographer (http://statgen.ncsu.edu/qtlcart/WQTLCart.htm; Wang et al, 2006) was done to identify the flanking markers and to estimate the likelihood of a QTL and its effect at 2 cM intervals with 10 cM windows.…”
Section: Qtl Mappingmentioning
confidence: 99%
“…1). The markers were developed based on the genomic DNA sequence of B. rapa cultivar Chiifu available at www.brassica.bbsrc.ac.uk/BrassicaDB (Kebede et al, 2012). 2, Table 4).…”
Section: Qtl Mappingmentioning
confidence: 99%